Breeding biology of Charybdis (Charybdis)feriatus (Linnaeus) from Mangalore - Babu, K V Ramesh; Benakappa, S; Mohan, K Chandra; Naik, A T Ramachandra (Indian Journal of Fisheries, 2011)
The computed Chi-square values indicated that male and female ratio inpopulation was not significant (P<0.05) during all the months of the year exceptNovember, whereas among different size groups a significance was observed.Dominance of male was noticed in almost all the size groups. Significant Chi-square values were observed in 61-65, 66-70 and 101-105 mm carapace width(CW) ranges. The fecundity varied from 35,635 to 3, 49,939 with an average of 1,42,012. The correlation value was found to be significant at p< 0.001 betweenthe parameters studied. The productivity index was found to increase from alow of 0.35 in 80 - 90 mm CW to a maximum of 2.78 in 110 - 120 mm CW.